Prevalence and spatial distribution of workplace violence against emergency medical staff in China: a cross-sectional study - Ruofan ZHANG; Jing FENG; Ge QU; Xinyan LI; Zihui LEI; Yuchao SUN; Aoqi SHEN; Chuanzhu LV; Xingyue SONG; Yong GAN (Zhongguo gonggong weisheng)
ObjectiveThis study aimed to analyze the prevalence and spatial distribution of workplace violence (WPV) in emergency departments (EDs) in China, to identify national trends and high-incidence areas, and to provide scientific evidence for the government to formulate and implement relevant intervention measures. MethodsA multi-stage random sampling method was used to conduct a survey of 34 819 ED medical staff in 31 provincial administrative regions in China from July to September 2019. The spatial distribution of WPV was explored based on geographic information system technology and spatial analysis methods. Data were analyzed using Stata 17.0 and GeoDa 1.18 software. ResultsThe average incidence of WPV in EDs in China was 84.16%, with the highest incidence of emotional abuse (80.43%), followed by threats and intimidation (59.96%), physical violence (42.11%), verbal harassment (30.54%), and physical harassment (15.27%). Spatial autocorrelation analysis showed that physical violence (Moran′s I = 0.246), threats and intimidation (Moran′s I = 0.092), and physical harassment (Moran′s I = 0.478) in WPV had significant spatial clustering relationships (all P < 0.05). The results of local spatial autocorrelation analysis showed that the high-incidence areas of WPV in EDs in China were mainly in the northwest and northeast regions, with the most serious situation in Inner Mongolia Autonomous Region, while the incidence rate in the southeast coastal areas of China was generally low. ConclusionsWPV among ED medical staff in China is serious, especially in the northwest and northeast regions, with significant spatial distribution differences, which urgently needs the attention of relevant departments.